O maestro Joaquim José de Mendanha : música, devoção e mobilidade social na trajetória de um pardo no Brasil oitocentista - Marques, Leticia Rosa (2017)
This thesis aims to analyze some of the limitations and possibilities of preservation and social ascension for the considered men of color in the nineteenth century in Brazil. As such, the trajectory of the mulatto teacher, Joaquim José de Mendanha, has become the main axis of this work. Following his spatial displacement throughout the Empire, as well as the different contexts (social, political, racial, cultural) in which he was immersed. Through this teacher, we seek an incursion through the ways of music, military careers and religious associations, analyzing some of the possible social spaces for mulattos of this period. Thus, through out the chapters, we will highlight the elements that led to this character to become an important reference in the music scene of Rio Grande do Sul State, inquiering what color meant/ represented, not just as a chromatic reference, but as a social place where such characteristics /elements would be necessary to be activated for a possible mobility in the period of the nineteenth century.